Pituitary gigantism: update on molecular biology and management. Issue 1 (February 2016) - Lodish, Maya B.; Trivellin, Giampaolo; Stratakis, Constantine A.
Abstract : Purpose of review: To provide an update on the mechanisms leading to pituitary gigantism, as well as to familiarize the practitioner with the implication of these genetic findings on treatment decisions. Recent findings: Prior studies have identified gigantism as a feature of a number of monogenic disorders, including mutations in the aryl hydrocarbon receptor interacting protein gene, multiple endocrine neoplasia types 1 and 4, McCune Albright syndrome, Carney complex, and the paraganglioma, pheochromocytoma, and pituitary adenoma association because of succinate dehydrogenase defects. We recently described a previously uncharacterized form of early-onset pediatric gigantism caused by microduplications on chromosome Xq26.3 and we termed it X-LAG (X-linked acrogigantism). The age of onset of increased growth in X-LAG is significantly younger than other pituitary gigantism cases, and control of growth hormone excess is particularly challenging. Summary: Knowledge of the molecular defects that underlie pituitary tumorigenesis is crucial for patient care as they guide early intervention, screening for associated conditions, genetic counseling, surgical approach, and choice of medical management. Recently described microduplications of Xq26.3 account for more than 80% of the cases of early-onset pediatric gigantism. Early recognition of X-LAG may improve outcomes, as successful control of growth hormone excess requires extensive anterior pituitary resection and are difficult to manage with medical therapy alone.